Energy, Economic Growth, and Financial Development in ASEAN+3 - Kartika Pramahesti; Djoni Hartono (Faculty of Economic and Business Syarif Hidayatullah State Islamic University of Jakarta, 2020)
This research aimed to determine the effects of financial development on the consumption of energy through the economic growth channels in ASEAN+3 in 1990 – 2013. Whether or not the financial development affected the energy consumption directly is still unclear, depending on how the efficiency of economic development takes place. The present research tried to complete the slit by evaluating the indirect effects of financial development through economic growth. The GMM method was applied to solve the endogenic problem of the simultaneous equation, resulting in an unbiased and consistent estimator. There was significant positive leverage of both the economic development and urbanization on the utilization of energy, while the cost of energy adversely affected its utilization. Also, there was a significant positive effect of financial growth in banking and share market on the utilization of energy, where the effect of the banking sector was stronger than that of the share market.JEL Classification: O13, O57, Q43How to Cite:Pramahesti, K., & Hartono, D. (2020). Energy, Economic Growth, and Financial Development in ASEAN+3. Signifikan: Jurnal Ilmu Ekonomi, Vol. 9(1), 137-152. doi: http://dx.doi.org/10.15408/sjie.v9i1.13536